High level phytase production by aspergillus niger NCIM 563 in solid state culture: response surface optimization, up-scaling, and its partial characterization - Bhavsar, Kavita P.; Kumar, V. Ravi; Khire, Jayant Malhar (Journal of Industrial Microbiology & Biotechnology, 2011)
Phytase production by Aspergillus niger NCIM 563 was optimized by using wheat bran in solid state fermentation (SSF). An integrated statistical optimization approach involving the combination of Placket-Burman design (PBD) and Box-Behnken design (BBD) was employed. PBD was used to evaluate the effect of 11 variables related to phytase production, and five statistically significant variables, namely, glucose, dextrin, NaNO(3), distilled water, and MgSO(4)center dot 7H(2)O, were selected for further optimization studies. The levels of five variables for maximum phytase production were determined by a BBD. Phytase production improved from 50 IU/g dry moldy bran (DMB) to 154 IU/g DMB indicating 3.08-fold increase after optimization. A simultaneous reduction in fermentation time from 7 to 4 days shows a high productivity of 38,500 IU/kg/day. Scaling up the process in trays gave reproducible phytase production overcoming industrial constraints of practicability and economics. The culture extract also had 133.2, 41.58, and 310.34 IU/g DMB of xylanase, cellulase, and amylase activities, respectively. The partially purified phytase was optimally active at 55A degrees C and pH 6.0. The enzyme retained ca. 75% activity over a wide pH range 2.0-9.5. It also released more inorganic phosphorus from soybean meal in a broad pH range from 2.5 to 6.5 under emulated gastric conditions. Molecular weight of phytase on Sephacryl S-200 was approximately 87 kDa. The K (m) and V (max) observed were 0.156 mM and 220 mu m/min/mg. The SSF phytase from A. niger NCIM 563 offers an economical production capability and its wide pH stability shows its suitability for use in poultry feed.
Keywords: Aspergillus niger; Phytase; Response surface optimization; Solid state fermentation; Statistical methods